Psychological effects of energy gels: An investigation into runners’ energy gel choice and consumption strategies in marathon running - Armağan Karahanoğlu (International Journal of Food Design, 2022)
Marathon running is a physical and mental activity. Runners consume high-energy food products to fill their glycogen stores for maintaining their marathon performance. This makes consuming carbohydrates, mainly in the form of energy gels, an essential part of marathon running. While previous research demonstrates significant physiological effects of these high-energy food products on performance, their psychological effects, which could benefit from and shed light on food design studies, have been underexplored. This article explores these effects with two participant studies, a narrative study (nn